SPAMUF: a behaviour-based maintenance prediction system - Bastos, Pedro (2012)
Advances in Safety, Reliability and Risk Management contains the papers presented at the 20th European Safety and Reliability (ESREL 2011) annual conference in Troyes, France, in September 2011.